Evaluación del afrecho de malta generado en la industria cervecera como sustrato del hongo Ganoderma Lucidum para la producción de un biomaterial (2025)
The aim of this research was to evaluate malt bran as a substrate for the cultivation of the fungus Ganoderma lucidum to produce biomaterials, addressing the issue of brewer's bran as a waste product in the brewing industry and exploring its potential in biotechnology. Throughout the research, different substrate formulations were evaluated, composed of malt bran and its hydrolysate, adjusted to concentrations of 45%, 35% and 25% malt bran and 55%, 65% and 75% hydrolysate. The substrate pH was maintained in an adequate average range of 5.57, without affecting the growth of the fungus, it was ground to improve its consistency and hydrated with a chemically adapted bran hydrolysate. Three tests of each substrate formulation were performed (A45:H55, A35:H65 and A25:H75). The A35:H65 formulation showed better mycelial colonization.